Identification of stable resistant donors against necrosis inducing strain of bean common mosaic virus in common bean (Phaseolus vulgaris L.). (2nd October 2021) - Manjunatha, L.; Basavaraja, T.; Manjunatha, N.; Srinivasa, N.; Kumar, Vijay; Chandora, Rahul; Singh, Mohar; Singh, N. P.
Abstract: Most of the commercially approved cultivars of Phaseolus vulgaris were susceptible to bean common mosaic virus (BCMV) which results in severe reduction in yield. In the present study, a total of 350 common bean genotypes were screened under natural epiphytotic conditions and artificial inoculation during 2016–2017, 2017–2018 and 2018–2019. Only eleven genotypes viz., EC400445, EC400414, ET4515B, EC540173, IC360831, BD9116291, EC31084, EC541703, ET8409, IC340947 and IC356024 were found stable resistant. The BCMV infection was confirmed through reverse-transcription polymerase chain reaction using coat protein gene amplification. The amplified region was sequenced and analyzed. Percent identity of BCMV-K with reported BCMV strains from different parts of world and based on nucleotide sequence ranged between 94% and 99.70% and maximum identity (99.70%) is observed with the strains of Uttar Pradesh (MT265069) and Himachal Pradesh (FJ387162, EU492546). The identified resistant sources from this study could be utilized as donors to develop BCMV resistant common bean cultivars.